Whose Embryo Is It Anyway?: The Need for a Federal Statute Enforcing Frozen Embryo Disposition Contracts. (23rd October 2017) - Faver, Alexandra
Abstract : Affording a couple the right to decide what should become of their frozen embryos in the event they divorce is of the utmost importance. The right to procreate, as well as not to procreate, has been observed as a constitutionally protected right under the Fourteenth Amendment of the U.S. Constitution. The interference by the judiciary in overriding, superseding, or simply ignoring disposition contracts is severely problematic. The parties have theoretically decided the best course of action by addressing potential future complications in disposition contracts. Not enforcing disposition contracts creates a lack of trust between the in vitro fertilization (IVF) facility and the parties and between the parties themselves. Knowing the contract they are signing may be thrown out if one party changes their mind, severely undermines contractual authority in assisted reproductive technology. This Note proposes multiple psychological, legal, and medical safeguards to be implemented by IVF facilities in order to ensure the parties enter into a valid and enforceable contract. Key Points for the Family Court Community: Only a handful of states have statutes addressing the enforcement of disposition contracts, some of which are at odds with one another. There is currently no federal statute in place that addresses this issue. Millions of Americans struggle with infertility issues every year. The average age for new parents over the years has increased while the decline in fertility based on age has not changed. As IVF treatments, as well as divorce rates, continue to increase, this issue will only become more prevalent in courts around the country. Creating a federal statute enforcing disposition contracts will afford parties engaging in IVF treatments resulting in frozen embryos to have the autonomy to make decisions regarding potential future complications, including divorce. Some state statutes in place provide a firm foundation for what should be included in a federal statute; however, they should be combined and expanded to include psychological awareness and ensure that each participant is substantively and procedurally protected.